Buton Cultural Potential in Curriculum Policy Development of Early Childhood Education Unit in Baubau City - Asma Kurniati; Andi Agustang (Universitas of Muhammadiyah Makassar, 2022)
This study aims to determine the potential of Buton culture in developing curriculum policies in the PAUD unit in Baubau City. In this study, the method used is qualitative, located in the city of Baubau. The technique of extracting data is through observation, interviews, and documentation. The study results show that Baubau City is a historical place rich in Buton cultural heritage and has become a tool for harmonization and harmony of diversity that has existed for hundreds of years. Buton culture is not tangible and intangible, so this potential must be preserved, developed, and integrated in a systematic and structured manner, namely through learning activities in the PAUD unit in its development in the PAUD unit, the Buton culture is creatively integrated into appropriate learning themes. . It is hoped that early childhood will have the potential of the Buton cultural character so that the Baubau City Government as a regional policyholder needs to formulate policies as a reference for developing a local curriculum based on Butonnese culture in PAUD units throughout the city of BaubauPenelitian ini bertujuan untuk mengetahui potensi budaya Buton dalam pengembangan kebijakan kurikulum di satuan PAUD Kota Baubau. Dalam penelitian ini, metode yang digunakan adalah kualitatif yang lokasinya di kota Baubau. Teknik penggalian data yang dilakukan adalah melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa Kota Baubau adalah tempat bersejarah yang kaya akan warisan budaya Buton dan menjadi alat harmonisasi serta kerukunan keberagaman yang telah ada sejak ratusan tahun yang lalu. Budaya Buton ini tada yang bersifat tangible dan intangible menjadi potensi ini harus dilestarikan, dikembangkan, dan diintegrasikan secara sistematis dan terstruktur yaitu melalui kegiatan pembelajaran di satuan PAUD dalam pengembangannya di satuan PAUD, budaya Buton tersebut diintegrasikan secara kreatif ke dalam teman-tema pembelajaran yang sesuai.Diharapkan anak usia dini kelak memiliki karakter budaya Buton yang petensial tersebut. Sehingga Pemerintah Kota Baubau sebagai pemegang kebijakan daerah perlu untuk menyusun kebijakan sebagai acuan pengembangan kurikulum lokal berbasis budaya Buton di satuan PAUD se kota Baubau.